Pengaruh Teknologi Digital Terhadap Pola Belajar Siswa Madrasah: Perspektif Pendidikan Islam di Era Digital - Al Nazwan Tahrizi; Taufik Johari; Khairun Nawawi; Masyitah Masyitah; Nazila Husna (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study aims to examine the influence of digital technology on the transformation of learning patterns among madrasah students from the perspective of Islamic education. With the increasing use of digital devices such as smartphones, tablets, and computers in learning activities, it is expected to affect students’ strategies, motivation, and learning efficiency. The methodology employed is a literature review, analyzing relevant sources related to educational technology within the context of madrasahs. The findings indicate a positive correlation between digital technology and learning motivation, independent learning ability, and adaptability to innovative instructional methods. In the framework of Islamic education, the use of technology must also be oriented towards reinforcing religious values, discipline, and ethical behavior in the learning process. These findings highlight the importance of integrating digital technology wisely into madrasah education systems to enhance educational quality in a way that is both adaptive and aligned with Islamic principles. The study recommends enhancing teachers' capacities in utilizing digital tools based on Islamic values and developing a madrasah curriculum that is responsive to the challenges of the digital era.